Fabrication of Highly-integrated Thermoelectric Generators Based on Ionic Liquids. (2015) - Uhl, Stefanie; Pellet, Michaël; Tschanz, Jessica; Laux, Edith; Journot, Tony; Jeandupeux, Laure; Keppner, Herbert
Abstract: Recent research in Ionic Liquids as new thermoelectric materials[1, 2] demands a suitable implementation in an industrially producible generator. Such a flexible micro generator can harvest electrical energy in order to extent battery lifetime or serve as single energy source for medical and wearable applications. The paper presents the fabrication steps of a new, highly integrated thermoelectric generator (TEG) based on ionic liquids. Furthermore, the applicability of ionic liquids with copper electrodes in thermoelectric devices is shown due to a passivation process at the electrode surface, whichallows the usage of commercially available copper clad laminates.